'An end to the job as we know it': how an IT professional has experienced the uncertainty of IT outsourcing. (June 2017) - Trusson, Clive; Woods, Frankie
This article foregrounds the voice of an IT professional who is directly employed by a large British company and who, along with colleagues, is experiencing career uncertainty resulting from a management initiative to replace the established workforce with an alternative labour supply provided by a global IT services company. As an account that reflects the uncertainty of the age, the narrative offers insights into current discussions concerning the contemporary nature and experience of work generally. More specifically it tells of a loss of confidence and status of technical professionals as they are methodically undermined by the confident assertion of a 'shareholder value' rhetoric. The suggestion is made that the application of commercial–professional rationality to the outsourcing of IT operations may underestimate the commercial risks associated with the loss of embodied technical knowledge gained across time as IT systems evolve to become complex constructions.